IMPLEMENTASI KOMPETENSI KEPRIBADIAN GURU PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR SWASTA BAKTI LUHUR MEDAN - Muhammad Azwar Effendi Ammar (Pascasarjana UIN Sumatera Utara, 2017)
Abstract: This research is generally intended to describe the Implementation of PAI Teacher PersonalityCompetence in Private Elementary School Bakti Luhur Medan. However, in particular this study aims todescribe the implementation of personality competence of PAI teachers in Private Primary School BaktiLuhur Medan, with details to describe: 1) How PAI teachers display honest personality, noble characterand role model for learners 2) PAI teachers show a steady, stable, mature, wise, and dignified personalityand community, 3) How important and meaningful is the work ethic, responsibility, and pride of beingthe PAI teacher for the PAI teacher. The type of research used in this thesis uses qualitative researchmethods and approaches conducted using naturalistic approaches. The informants in this study are PAIteachers, principals, private primary school Bakti Luhur Medan, and two other informants namely PKSI in the field of curriculum and PKS II student field. Data obtained from two sources are primary datasources and secondary data sources with data collection techniques through observation, interviews (freeinterview, guided interviews and free guided interviews) and documentation. The data analysis techniqueis done by data reduction, categorization, sintesisasi, arranging work hypothesis. To ensure the validity ofthe data, the researcher uses in-depth observation, triangulation (triangulation data, triangulation bymethod, and source triangulation) is defined as data collection techniques that combine from variousdata collection techniques and data sources that already exist.